Risk Management for Florida 4-H Youth Development Work: Large Animals — Livestock - Chad Carr; Sandra TenBroeck; Dale Pracht; Georgene Bender; Amber Norris; Candi Dierenfield (EDIS)
This is one part of the series Risk Management for 4-H Youth Development Work.